Maternal risk factors for gastroschisis in Canada. Issue 2 (12th February 2015) - Skarsgard, Erik D.; Meaney, Christopher; Bassil, Kate; Brindle, Mary; Arbour, Laura; Moineddin, Rahim; ,
Abstract : Background: Gastroschisis is a congenital abdominal wall defect that occurs in one per 2200 pregnancies. Birth defect surveillance in Canada has shown that the prevalence of gastroschisis has increased threefold over the past 10 years. The purpose of this study was to compare maternal exposures data from a national gastroschisis registry with pregnancy exposures from vital statistics to understand maternal risk factor associations with the occurrence of gastroschisis. Methods: Using common definitions, pregnancy cohorts were developed from two databases. The Canadian Pediatric Surgery Network database, a population‐based dataset was used to record maternal exposures for women who experienced a gastroschisis pregnancy, while a contemporaneous, geographically cross‐sectional "control" cohort of pregnant women and their exposures was developed from Canadian Community Health Survey data. Groups comparison of maternal risk factors was performed using univariate and multivariate logistic generalized estimating equation techniques. Results: A total of 692 gastroschisis pregnancies (from Canadian Pediatric Surgery Network) and 4708 pregnancies from Canadian Community Health Survey were compared. Younger maternal age (odds ratio, 0.85; 95% confidence interval, 0.83–0.87; p < 0.0001), smoking (odds ratio, 2.86; 95% confidence interval, 2.22–3.66; p < 0.0001), a history of pregestational or gestational diabetes (odds ratio, 2.81; 95% confidence interval, 1.42–5.5; p = 0.0031), and use of medication to treat depression (odds ratio, 4.4; 95% confidence interval, 1.38–11.8; p = 0.011) emerged as significant associations with gastroschisis pregnancies. Conclusion: Gastroschisis in Canada is associated with maternal risk factors, some of which are modifiable. Further studies into sociodemographic birth defect risk are necessary to allow targeted improvements in perinatal health service delivery and health policy. Birth Defects Research (Part A) 103:111–118, 2015 © 2015 Wiley Periodicals, Inc.